Strengthening Computational Thinking through Innovative STEAM Activities in Early Childhood Education - Fatonah, Berliana Siti; Mulyana, Edi Hendri; Sianturi, Risbon (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study aims to describe the strengthening of computational thinking through innovate STEAM activities in early childhood at Joy Kids National Plus. The background of the study is the importance of building logical and systematic thinking patterns from an early age through a fun and integrated learning approach. The study used a qualitative approach with a case study method. Data collection techniques include observation, interviews, and documentation. The result showed that STEAM activities at Joy Kids Kindergarten were designed in the form of simple projects that combine elements of science, technology, engineering, art, and mathematics. The teacher’s strategy in facilitating activities provides space for exploration, collaboration, and reflection. Children demonstrate computational thinking skills such as recognizing patterns, solving problems, and compiling solution steps. Teachers have a positive perception of the implementation of STEAM, despite technical challenges. Overall, the STEAM approach is effective in forming the basis of computational thinking in early childhood.